Phaco Time Phaco-Horizontal-Chop Technique for Cataract Surgery with Various Degrees of Lens Hardness - Imam Masduki; Dwi Ditha Emelia; Ahmad Ikliluddin (Ahmad Dahlan Medical Journal, 2022)
The most frequent and accurate cataract surgery had been the phacoemulsification method. Currently, phacoemulsification had been developed using various techniques including divide and conquer phaco chop and supra capsular. This research aims to assess the cataract surgery time or phaco time at various degrees of lens hardness. All cataract patients at the Kharisma Paramedika Hospital, Kulon Progo, Yogyakarta Special Region during the period June-December 2021, had cataract surgery using the horizontal chop phacoemulsification technique, by an experienced eye specialist. The machine used the Millennium from Bausch & Lomb. Parameter settings on the machine are as follows: bottle height 100 cm; vacuum 230 mmHg; 25% power; multi burst module. The patient gave topical anesthesia with 0.5% pantocaine, then an incision was made with 2.75 mm keratoma, then trypan blue gave into the anterior chamber of the eye, then sodium hyaluronate was added without rinsing. Then the operator performs an anterior capsulotomy in a way of continuous circular capsulorhexis (CCC). The second port incision was made with a 15-degree knife, then hydro dissection was performed. The phaco time value was recorded on the machine at the end of each operation. There were 40 subjects (57%) male and 30 subjects (43%) female. Subjects aged 50-65 years reached 56 subjects (80%) and those aged >65 years were 14 subjects (20%). The average value of phaco time was obtained at 54.83 seconds. As Conclusion, Phacoemulsification cataract surgery with horizontal chop technique at various degrees of resolution density obtained an average phaco time of 54.83 seconds. ABSTRAK Pembedahan katarak yang cukup akurat dilakukan adalah dengan metode fakoemulsifikasi. Berbagai teknik fakoemulsifikasi, antara lain: divide and conquer, phaco chop (terdiri dari: horizontal chop, vertical chop, serta stop&chop), dan suprakapsular. Teknik horizontal chop dan vertical chop cukup efektif dilakukan, namun teknik ini cukup sulit bagi pemula. Terdapat parameter yang dapat dinilai pada operasi katarak, salah satunya yaitu phaco time. Penelitian ini bertujuan menilai waktu operasi katarak atau phaco time pada berbagai derajat kekerasan lensa. Semua pasien katarak di RS Kharisma Paramedika, Kulon Progo, Daerah Istimewa Yogyakarta (DIY), selama periode Juni-Desember 2021, dilakukan operasi katarak dengan teknik fakoemulsifikasi horizontal chop, oleh seorang spesialis mata yang sudah berpengalaman. Mesin yang digunakan adalah Millenium dari Bausch & Lomb. Parameter pengaturan pada mesin sebagai berikut : tinggi botol 100 cm ; vacum 230 mmHg ; power 25% ; modul multiburst. Pada pasien diberikan anestesi topikal dengan pantocain 0,5%, selanjutnya dilakukan insisi dengan keratom 2,75 mm, diberikan trypan blue ke dalam kamera okuli anterior, kemudian tanpa pembilasan dimasukkan sodium hyaluronat. Operator melakukan kapsulotomi anterior dengan cara continuous circular capsulorhexis (CCC). Pembuatan insisi second port dilakukan dengan pisau 15 derajat, lalu dilakukan hidrodiseksi. Pencatatan nilai phaco time dilakukan setiap akhir operasi. Hasil penelitian kami, sebanyak 70 subjek penelitian, terdiri dari 40 subjek (57%) laki-laki dan 30 subjek (43%) perempuan. Subjek yang memiliki usia 50-65 tahun berjumlah 56 subjek (80%) dan yang berusia >65 tahun berjumlah 14 subjek (20%). Nilai rata-rata phaco time yang didapatkan adalah 54,83 detik.  Sehingga dapat kami simpulkan operasi katarak fakoemulsifikasi dengan teknik horizontal chop pada berbagai derajat kepadatan lensa didapatkan nilai rata-rata phaco time sebesar 54,83 detik.